(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
ABSTRACT Background: High levels of C-reactive protein (CRP), an acute phase reactant, that has been proven to be associated with decreased clinical outcome in small-scale in Diffuse large B-cell lymphoma (DLBCL). The aim of this study was to evaluate the prognostic impact of pretreatment CRP levels on overall survival (OS) and progression free survival (PFS) of DLBCL patients. Methods: Data from 117 DLBCL patients, diagnosed and treated between 2010 and 2016 in Tishreen University Hospital, were evaluated retrospectively. The prognostic influence of CRP and other factors, including age, tumor stage, LDH, extra nodal involvement, and international Prognostic Index (IPI) on 5-year OS and 5-year PFS, were studied by Kaplan-Meier curves as well as univariate and multivariate Cox regression models. Results: Kaplan-Meier curves revealed elevated CRP as a factor for decreased 5-year OS (P=0.002, log-rank test) and PFS in DLBCL patients (P<0.001, Log-rank test). An independent significant association between high CRP levels and poor clinical outcome in multivariate analysis for 5-year OS (HR=6.36, CI95%=1.75-23.13, P=0.005) and for PFS (HR=4.18, CI95%=1.91-9.16, P<0.001). we demonstrated high CRP levels at diagnosis of DLBCL as an independent poor prognostic factor for clinical outcome. Key Words: Diffuse large B cell lymphoma, C-reactive protein, IPI